Intraabdominal hypertension/abdominal compartment syndrome after pelvic fractures: How they occur and what can be done?. Issue 4 (April 2019) - He, Li; Yi, Chengla; Hou, Zhiyong; Hak, David J.
Highlights: The pelvic fracture type does not seem to have a significant effect on IAP level. IAH/ACS that develops in pelvic fracture patients is commonly due to 'polycystic' retroperitoneal hematoma or swollen bowel. The prophylactic/therapeutic DL significantlly improved the physiological parameters in pelvic fracture patients with IAH/ACS. Prophylactic DL is important for decreasing mortality as it prevents IAH from progressing to ACS. The massive fluid resuscitation is a significant risk factor for IAH/ACS and should be optimized in pelvic fracture patients. Abstract: Background: Limited data exist regarding intraabdominal hypertension/abdominal compartment syndrome (IAH/ACS) after pelvic fractures. We aimed to explore risk factors for IAH/ACS in pelvic fracture patients, assess the physiological effects of decompressive laparotomy (DL) on IAH/ACS, and generate an algorithm to manage IAH/ACS after pelvic fracture. Materials and methods: Pelvic fracture patients were included based on the presence of IAH/ACS. Intraabdominal pressure (IAP) was measured through a Foley catheter. DL was performed in patients with refractory IAH or ACS. Multivariable linear regression was applied to assess associations between IAP levels (≥12 mmHg) and age, sex, injury severity score (ISS), pelvic fracture, volume of resuscitation fluids over 24 h and hemoglobin values. The Wilcoxon signed-rank test for paired samples was used to compare variables before and after DL. Results: Among 455 pelvic fracture patients, 44 (9.7%) and 5 (1.1%) were diagnosed with IAH and ACS, respectively. The volume of resuscitation fluids over 24 h exhibited a significant positive correlation with IAP levels (≥12 mmHg) (p = 0.002). The main findings during DL were edematous bowel (11/20) and retroperitoneal hematoma (7/20). DL caused a significant decrease in the mean IAP from 24.4 ± 8.5 mmHg to 13.4 ± 4.0 mmHg (p < 0.0001). Physiological parameters (APP, PaO2/FIO2 ratio, PIP, arterial lactate and UOP) were significantly improved after DL. The mortality rate was 15% in patients who underwent DL and 40% in ACS patients. Conclusions: IAH/ACS is common in pelvic fracture patients. The most effective method to decrease IAP in pelvic fracture patients is DL. Prophylactic DL is important for decreasing mortality as it prevents IAH from progressing to ACS. Massive fluid resuscitation is a significant risk factor for IAH/ACS. A pathway incorporating prophylactic/therapeutic DL and optimized fluid resuscitation to prevent and manage IAH/ACS after pelvic fractures may reduce morbidity and mortality.